Estruturas de gerenciamentos de riscos corporativos em bancos públicos federais - Palácio, Renato de Castro (2023)
Starting from current Corporate Governance practices, the development of theories on Corporate Risk Management (CRM) can be observed, with definitions, guidelines, mechanisms, instruments, and models for managing situations of uncertainty that may negatively impact company performance. Particularly in the banking sector, CRM practices are widely adopted, largely due to national and international regulatory pressures to which the sector is subject. From the perspective of Institutional Isomorphism, this research aims to highlight manifestations of isomorphism in risk management practices adopted by Brazilian federal public banks. The research used Risk Management - Pillar 3 reports released by the companies as source material. In total, the research identified in the CRM practices reported by the 5 (five) banks researched, 18 (eighteen) evidence of institutional isomorphy of the coercive type and 2 (two) evidence of a normative type. Therefore, concluding that there is a prevalence of homogeneity in corporate risk management practices of Brazilian Federal Public Banks, due to the strong regulation to which these companies are subject in the development of their activities